The Effectiveness of Metacognitive Skills Training on Enhancing Crystallized Intelligence in Secondary School Students - Goran Savadkohi , Laden; Kamyab, Mitra; Seadatee Shamir, Aboutaleb; Andishmand, Vida (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to determine the effectiveness of metacognitive skills training on enhancing crystallized intelligence in lower secondary school students (ages 13 to 15) in public schools.Methods and Materials: The research design was a quasi-experimental study with a pretest-posttest control group framework. The research population comprised lower secondary school students in District 3, Tehran, during the 2023-2024 academic year. Using convenience sampling, 30 students were selected and randomly assigned to two groups: an experimental group (15 students receiving the metacognitive skills training program) and a control group. The experimental group underwent metacognitive skills training over eight sessions, each lasting 90 minutes. Data collection instruments included the Metacognitive Skills Training Program (Flavell, 1999) and the Crystallized Intelligence Test (Sa'adati Shamir & Zahmatkesh, 2023).Findings: The results of covariance analysis indicated that the metacognitive skills training package significantly enhanced crystallized intelligence in students aged 13 to 15. Metacognitive skills training for lower secondary school children improved their abilities in components such as personality intelligence, emotional intelligence, social intelligence, cultural intelligence, economic intelligence, managerial intelligence, philosophical intelligence, kinesthetic-motor intelligence, and eudaimonic intelligence. This training enhanced their self-efficacy for achieving higher goals, empowered them cognitively across various dimensions, and better prepared them for a more enriched future. Additionally, students who received more detailed and comprehensive metacognitive skills training experienced greater social support. As a result, they performed better in the components of skilled crystallized intelligence, including personality intelligence, emotional intelligence, social intelligence, cultural intelligence, economic intelligence, managerial intelligence, philosophical intelligence, kinesthetic-motor intelligence, and eudaimonic intelligence. Consequently, these students demonstrated better academic performance, held a more positive attitude toward education, and reported greater overall satisfaction with school.Conclusion: In summary, self-esteem enhancement through the development of crystallized cognitive abilities leads to increased academic success and resilience.